2002
DOI: 10.2320/matertrans.43.1089
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Dependence of Hydrogen-Induced Amorphization in C15 Laves Phase TbFe<SUB>2</SUB>

Abstract: The pressure dependence of structural changes of C15 Laves phase TbFe 2 heated in a hydrogen atmosphere was investigated using a pressure differential scanning calorimeter (PDSC), a powder X-ray diffractometer (XRD), a differential scanning calorimeter (DSC) and a hydrogen analyzer. Hydrogen absorption in the crystalline state, hydrogen-induced amorphization (HIA), precipitation of TbH 2 and decomposition of the remaining amorphous alloy into α-Fe and TbH 2 occurred exothermally with increasing temperature abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Recently, the present authors have shown that C14 Laves phase NdMn 2 with the atomic size ratio R Nd /R Mn = 1.45 amorphizes also by hydrogenation [17]. Furthermore, it has been reported that structural changes in C15 Laves phases RFe 2 depend on the kind of R [12,13]. That is, hydrogen absorption, HIA, the precipitation of RH 3 and the decomposition of the remaining amorphous phase occur in RFe 2 (R = Sm, Gd, Tb, Dy and Ho).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Recently, the present authors have shown that C14 Laves phase NdMn 2 with the atomic size ratio R Nd /R Mn = 1.45 amorphizes also by hydrogenation [17]. Furthermore, it has been reported that structural changes in C15 Laves phases RFe 2 depend on the kind of R [12,13]. That is, hydrogen absorption, HIA, the precipitation of RH 3 and the decomposition of the remaining amorphous phase occur in RFe 2 (R = Sm, Gd, Tb, Dy and Ho).…”
Section: Introductionmentioning
confidence: 86%
“…HIA has been observed in the intermetallic compounds A x B 1−x consisting of hydride forming (A) and non-hydride forming metals (B) with the crystal structures such as C15, B8 2 , C23, D0 19 and L1 2 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Among these, structural changes in the C15 Laves phases RFe 2 (R = rare earth metals) are particularly interesting, because both a crystalline and an amorphous hydride form depending on the hydrogenation temperature [12]. One of the present authors (Aoki) investigated hydrogen-induced structural changes in C15 Laves phases AB 2 and demonstrated that HIA occurs in the compounds having the atomic size ratio larger than 1.37 [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that crystalline hydrides c-RM 2 H x can desorb hydrogen in the crystalline state and their Ar-DSC curves show only endothermic peaks at relatively low temperatures without exception. 14,15,18,19) The Ar-DSC curve of DyCo 2 heated to above the first The sample heated to above the first exothermic peak (to 400 K) (a,b), the second peak (to 623 K) (c), the third peak (to 723 K) (d) and to the fourth peak (to 798 K) (e).…”
Section: Structural Changes Of Dyco 2 Heated In a Hydrogenmentioning
confidence: 99%
“…Furthermore, T p of HIA for C15 Laves RFe 2 (R ¼ Tb, Er) shows also a same strong negative pressure dependence. [15][16][17][18] It has been proposed that HIA of C15 Laves RM 2 occurs by the short-range diffusion of R and M atoms. Therefore, it is interesting to compare the pressure dependence of HIA for DyCo 2 with that for DyFe 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Among amorphizing compounds, structural changes in the C15 Laves compounds RFe 2 (R = rare earth metals) are particularly interesting, because a crystalline and an amorphous hydride are formed depending on the hydrogenation temperature [7]. More recently, it has been reported that HIA in both TbFe 2 and ErFe 2 occurs at a given hydrogen pressure or higher pressures [12][13][14][15], but that HIA in CeFe 2 does ocevacuated quartz tube. After the homogenization, the ingot was crushed into 100 mesh in acetone to prevent oxidation and ignition.…”
Section: Introductionmentioning
confidence: 99%